Making Medicines in Africa The Political Economy of Industrializing for Local Health - Mackintosh, Maureen; Banda, Geoffrey; Tibandebage, Paula; Wamae, Watu (Springer Nature, 2015)
Life Sciences, Pharmacology and Toxicology, Economics, Political Economy, Development, International Relations, International Political Economy, African Studies, African Economics